State and society in the Philippines - Abinales, P. N.; Amoroso, Donna J., 1960-2011 (Lanham ; Boulder ; New York ; London : Rowman & Littlefield, 2017)
"Now in a fully updated edition that considers the controversial presidency of Rodrigo Dutarte, this comprehensive introduction to Philippine politics engages the dilemma of state-society relations through a historical treatment of state formation and the corresponding conflicts and collaborations between state leaders and social forces. The authors trace the long history of institutional state weakness in the Philippines and the efforts made to overcome the state's structural fragility and strengthen its bond with society. They answer these difficult questions by focusing on how the state has shaped and been shaped by its interaction with social forces, especially in the rituals of popular mobilization that have produced surprising and diverse results"--
Includes bibliographical references (pages 353-393) and index.
Keywords: Philippines -- Politics and government; Philippines -- Social conditions